Fine-tuning optimization for PV-PEMFC phased array system - Hatti, Mustapha; Kellil, Nouamen; Rahmani, Hachemi (2016 IEEE International Symposium on Phased Array Systems and Technology (PAST), 2016)
Thanks to optimization technology, we can quickly correlate and validate a simulation models using other references, such as experimental measurement data. Similarly, with the updated simulation model, it's easy to evaluate various designs to fine-tune specific functional performance characteristics of outcomes. Fine-tuning can be understood as "to find the set of parameters performing well on a wide set of instances". Help us to decide on critical design trade-offs between different constraints, quality, performance and cost aspects. The ultimate design relies on a calibrated simulation model that provides the expected accuracy throughout subsequent development stages. Heuristics algorithms, and their higher forms meta-heuristics, have been widely used to find reasonable good solutions of energetic problems. The performance of those heuristics is based on the optimum set-up of a set of parameters. The problem of fine-tuning those parameters is also a hard problem. The implementation of hybrid systems is very broad in the range of 50 kW to 250 kW. Energy storage may soon play a bigger part in our electricity grid, and help enable the increased generation of renewable electricity. An algorithm, using a Phased array framework, to optimize the parameters of the energetic hybrid system containing Photovoltaic-Proton exchange Fuel Cell is designed. The paper tackles the study of feasibility to implement phased array control into an energetic system and to optimize the membership functions of the fuzzy logic controller for the Photovoltaic-Proton exchange Fuel Cell phased array system using genetic algorithm (GA). The manuscript deals with a genetic algorithm control strategy purpose to generate electrical energy according to the request, subject to the constraints and the dynamics of the substantial load and intermittency of the energetic supply, by charring the power require among the photovoltaic array and the Photovoltaic - Proton exchange fuel cell system. PEM Fuel Cells is described specifically as well as system pattern and components parameters [1]. The next section committed to representing the mean process of genetic algorithm control for Photovoltaic-Proton exchange Fuel Cell Fuel Cell phased array System. Finally, the optimal control problem is addressed and phased array algorithm is introduced to facilitate locate a set of best parameters in the genetic algorithm controller, finest results are obtained and good optimization of the phased array system is highlighted.